The Influence of Cash Management Practices on the Growth of Small Medium Enterprises in East London, Eastern Cape Province, South Africa - Spekelet, Mudondo Consenta; Oni, Olabanji; Solomon, Omonona (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
The primary objective of the study was to determine the influence of cash management practice on the growth of Small Medium Enterprises (SMEs) in East London, Eastern Cape Province. The researcher utilizes a quantitative research approach and descriptive research design in order to determine the influence of cash management practices and the growth of SMEs. Simple random sampling was employed to select a sample size of 93 registered General Trading SMEs in East London. The study used Statistical Package for Social Sciences (SPSS) version 25 software to analyse data. Inferential statistics such as multiple regression and correlation were used to analyse data. The findings obtained discovered that cash management practices have a positive influence on growth of SMEs in East London, Eastern Cape Province. Recommendations emphasised that Managers of SMEs should be thoroughly trained on cash management skills. They should undergo developmental programs such as conference and open forums.